2013
DOI: 10.1681/asn.2012070730
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipase A2 Receptor (PLA2R1) Sequence Variants in Idiopathic Membranous Nephropathy

Abstract: The M-type receptor for phospholipase A2 (PLA2R1) is the major target antigen in idiopathic membranous nephropathy (iMN). Our recent genome-wide association study showed that genetic variants in an HLA-DQA1 and phospholipase A2 receptor (PLA2R1) allele associate most significantly with biopsy-proven iMN, suggesting that rare genetic variants within the coding region of the PLA2R1 gene may contribute to antibody formation. Here, we sequenced PLA2R1 in a cohort of 95 white patients with biopsy-proven iMN and ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
92
1
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(102 citation statements)
references
References 25 publications
4
92
1
5
Order By: Relevance
“…Current knowledge of the PLA2R sequence derived from gene sequencing suggests that the PLA2R protein structure in patients with IMN is not significantly different from that of healthy controls. 13 Other potential mechanisms affecting antigen conformation and aberrant immune processing need exploring to understand how PLA2R becomes immunogenic. We described a pH-dependent conformational change in PLA2R (N-C8), as previously reported for FcRY, 12 and show that this is not a property of the N-C3 fragment and does not influence the affinity of antibody interaction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Current knowledge of the PLA2R sequence derived from gene sequencing suggests that the PLA2R protein structure in patients with IMN is not significantly different from that of healthy controls. 13 Other potential mechanisms affecting antigen conformation and aberrant immune processing need exploring to understand how PLA2R becomes immunogenic. We described a pH-dependent conformational change in PLA2R (N-C8), as previously reported for FcRY, 12 and show that this is not a property of the N-C3 fragment and does not influence the affinity of antibody interaction.…”
Section: Discussionmentioning
confidence: 99%
“…2 It is unlikely that genetically determined amino acid changes in PLA2R specific to cases of IMN could influence immunogenicity or contribute to a 3D conformational disease epitope. 13 One study described linear epitopes within PLA2R using an overlapping array of short peptide sequences derived from PLA2R. 14 Seven linear peptides were tested using ELISA, but no difference was seen between IMN-seropositive patients and control sera.…”
mentioning
confidence: 99%
“…Interestingly, several common genetic variants associated with iMN have been localized in these domains. 25 CysR clearly appears as the primary dominant epitope with evidence for epitope spreading toward CTLD1 and CTLD7. Our results thus further extend those of Kao et al and Fresquet et al who identified epitopes in the CysR-CTLD1 region and CysR alone, respectively.…”
Section: Ctld7mentioning
confidence: 97%
“…This allele may facilitate an autoimmune response against antigenic targets such as variants of PLA2R1 (2). However, these variants were seen only in 4 of 60 patients with PLA2R1-associated MN, suggesting that these rare variants are unlikely to explain the pathogenesis of the disease (3). According to Salant (4), the development of idiopathic MN may be the result of three conditions: (1) the presence of HLA-DQA1 alleles that confer susceptibility to autoimmunity, (2) polymorphism of PLA2R1 that creates a unique conformation that can represent a target for autoantibodies, and (3) production of hypogalactosylated IgG4 anti-PLA2R1 that activates the mannan pathway of the complement.…”
Section: Introductionmentioning
confidence: 99%